Polyacrylonitrile carbon fiber precursor, preparation method thereof and carbon fiber

By using small molecule alcohol compounds as coagulation agents in the polyacrylonitrile carbon fiber raw silk preparation process to form dot-shaped gel dots and form a groove structure during the solidification and drafting process, the problems of complex equipment, high cost and poor interface bonding force in the existing process are solved, and efficient interlayer shear strength of spinning and strengthening composite materials are achieved.

CN119843380APending Publication Date: 2025-04-18CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202311353240.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing polyacrylonitrile carbon fiber raw silk preparation process has problems such as complex equipment and process flow, high cost and poor interface bonding power of composite materials.

Method used

A small molecule alcohol compound is used as a coagulant, and the fine stream of stock liquid formed by spinning is in contact with the coagulant in the air layer, and then enters the coagulant to solidify in the coagulant bath to form a dot-like distribution of gel dots, thereby forming a groove structure arranged in the axial direction of the fiber during the subsequent coagulation and drafting process.

Benefits of technology

The high spinning speed is maintained, and the groove structure is formed on the surface of the original wire, which improves the interlayer shear strength of the composite material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843380A_ABST
    Figure CN119843380A_ABST
Patent Text Reader

Abstract

The invention relates to the field of carbon fibers, and discloses a polyacrylonitrile carbon fiber precursor, a preparation method thereof and a carbon fiber. The method comprises the following steps: spinning stock solution is subjected to spinning to form stock solution trickles, the stock solution trickles are in contact with a coagulating agent in an air layer and then enter a coagulating bath to be coagulated; the coagulator is a small molecular alcohol compound. According to the method, the advantages of wet spinning and dry-wet spinning are combined, the high spinning speed can be kept, the groove structure can be formed in the surface of the protofilament, and then the interlaminar shear strength of the composite material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of carbon fibers, and in particular to a polyacrylonitrile carbon fiber precursor and a preparation method thereof, and the carbon fiber. Background Art

[0002] At present, the preparation of polypropylene carbon fiber precursor mainly adopts two processes: wet method and dry-wet method, each with its own advantages and disadvantages. In the wet process, the spinneret is immersed in a coagulation bath. After the spinning solution is extruded through the spinneret, it begins to solidify in the Balas expansion stage. The solidified cortex shrinks after stretching to form a groove structure arranged along the fiber axis. This structure continues to the finished precursor and carbon fiber. The groove structure is easy to produce an anchoring effect with the resin matrix when preparing composite materials, with good interface bonding and high interlayer shear strength. However, the spinning solution of this process begins to solidify in the extrusion expansion stage, and the tension on the coagulated filaments is large, and increases linearly with the spinning speed. When the speed is increased to a certain extent, the primary fiber breaks. Therefore, the speed of wet spinning is relatively low, generally below 200 meters / min. In the dry-wet spinning process, the spinning solution passes through a certain height of air layer after being extruded from the spinneret before entering the coagulation bath. The extrusion expansion effect is basically eliminated in the air layer, and the drafting point also occurs in the air layer during the coagulation and drafting process. Therefore, the coagulation tension is low, and it is easy to increase the spinning speed. The dry-wet spinning speed is generally 300-450 meters / min, which is conducive to increasing production and reducing production costs. However, since the dry-wet spinning eliminates the extrusion expansion effect in the air layer, the surface of the prepared raw silk and carbon fiber is smooth, and the interface bonding force is poor when preparing composite materials, and the interlayer shear strength is low.

[0003] Patent application CN104088029B provides a method for manufacturing polyacrylonitrile carbon fiber precursor, which forms a restricted space between the dry and wet spinning assembly and the coagulation bath surface in an isolated form, and uses petroleum ether, silicone oil and other non-coagulation baths to fill the air layer, that is, the spinning solution is first passed through a non-coagulation bath after being extruded through the spinneret and then enters the coagulation bath for coagulation. The patent believes that the use of this process can maintain the characteristics of fast spinning speed, reduce the risk of paste board, and a certain groove structure can also be formed on the fiber surface. However, the reason why the non-coagulant of this method causes the groove structure to form on the fiber surface is still unclear. Patent application CN109537106A uses a method similar to gel spinning to prepare PAN precursor at high speed, and can produce fibers with special cross-sections, but this method uses more alcohols as coagulants, the production cost is high, and the environmental pollution is more serious. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of complicated equipment and process flow, high cost and the like in the prior art, and to provide a polyacrylonitrile carbon fiber precursor and a preparation method thereof and a carbon fiber.

[0005] In order to achieve the above object, the present invention provides a method for preparing polyacrylonitrile carbon fiber precursor, the method comprising: a spinning solution formed by spinning a thin stream of the solution is contacted with a coagulant in an air layer, and then enters a coagulation bath for coagulation;

[0006] The coagulant is a small molecule alcohol compound.

[0007] Preferably, the small molecule alcohol compound is a C1-C5 fatty alcohol.

[0008] Preferably, the small molecule alcohol compound is selected from one or more of methanol, ethanol and n-propanol.

[0009] Preferably, the coagulant is coagulant droplets;

[0010] Preferably, the coagulant droplets are generated by an ultrasonic atomizer.

[0011] Preferably, the diameter of the coagulant droplets is 0.5-5 μm.

[0012] Preferably, the coagulant droplets are transported into the air layer by a carrier gas;

[0013] Preferably, the carrier gas is nitrogen.

[0014] Preferably, the height of the air layer is 3-10 mm, preferably 5-8 mm.

[0015] Preferably, the spinning solution is a dimethyl sulfoxide solution of polyacrylonitrile copolymer;

[0016] Preferably, the viscosity average molecular weight of the polyacrylonitrile copolymer is 80,000-150,000.

[0017] Preferably, the spinning solution is obtained by polymerizing a polymerizable monomer containing acrylonitrile in dimethyl sulfoxide;

[0018] Preferably, the content of the polymerized monomer is 19-22 wt % based on the total weight of the polymerized monomer and dimethyl sulfoxide;

[0019] Preferably, the content of acrylonitrile in the polymerized monomer is 97-99% by weight.

[0020] Preferably, the coagulation bath is an aqueous solution of dimethyl sulfoxide;

[0021] Preferably, the concentration of dimethyl sulfoxide in the coagulation bath is 25-35 wt %;

[0022] Preferably, the temperature of the coagulation bath is 2-10°C.

[0023] The second aspect of the present invention provides polyacrylonitrile carbon fiber precursor prepared by the method described above.

[0024] A third aspect of the present invention provides a carbon fiber, which is obtained by pre-oxidation and carbonization of the carbon fiber precursor described above.

[0025] The method for preparing polyacrylonitrile carbon fiber precursor described in the present invention introduces coagulant droplets with low coagulation value into the air layer, and the droplets contact the surface of the spinning solution stream extruded through the spinneret in the air layer to form gel points distributed in a dotted manner. The gel points are only distributed on the surface of the spinning solution stream, and will not affect the elimination of the extrusion expansion effect in the air layer and the spinneret drafting, so that a high spinning speed can still be maintained, and the gel points can form a groove structure arranged along the fiber axis in the subsequent coagulation and drafting process. The method described in the present invention combines the advantages of wet spinning and dry-wet spinning, can maintain a high spinning speed, and can form a groove structure on the surface of the precursor, which can improve the interlaminar shear strength of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is a schematic diagram of the spinning and coagulation device of the present invention;

[0027] Figure 2-3 is the SEM characterization result of the raw silk prepared in Example 1;

[0028] Figure 4-5 is the SEM characterization result of the raw silk prepared in Example 2;

[0029] Figure 6-7 This is the SEM characterization result of the raw silk prepared in Comparative Example 1.

[0030] Description of Reference Numerals

[0031] 1 Spinning assembly 2 Sealing cover

[0032] 3 coagulation bath 4 carrier gas tank

[0033] 5 Ultrasonic atomizer 11 spinneret

[0034] 21 entrance 31 godet roller DETAILED DESCRIPTION

[0035] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0036] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0037] In one aspect, the present invention provides a method for preparing polyacrylonitrile carbon fiber precursor, the method comprising: a spinning solution formed by spinning a thin solution stream is contacted with a coagulant in an air layer, and then enters a coagulation bath for coagulation;

[0038] The coagulant is a small molecule alcohol compound.

[0039] In a preferred embodiment, the small molecule alcohol compound is a C1-C5 fatty alcohol.

[0040] Further preferably, the small molecule alcohol compound is selected from one or more of methanol, ethanol and n-propanol.

[0041] In a preferred embodiment, the coagulant is in the form of coagulant droplets. The coagulant in the air layer exists in the form of coagulant droplets, which is conducive to the coagulant contacting the surface of the stock solution thin flow in the air layer to form gel points distributed in a dotted manner. The gel points are only distributed on the surface of the stock solution thin flow, which will not affect the elimination of the extrusion expansion effect in the air layer and the spinneret drafting, so that a high spinning speed can still be maintained.

[0042] In a preferred embodiment, the coagulant droplets are generated by an ultrasonic atomizer.

[0043] In a preferred embodiment, the diameter of the coagulant droplets is 0.5-5 μm, more preferably 1-3 μm.

[0044] In a preferred embodiment, the coagulant droplets are transported into the air layer by a carrier gas.

[0045] Further preferably, the carrier gas is nitrogen.

[0046] In a preferred embodiment, the height of the air layer is 3-10 mm, more preferably 5-8 mm.

[0047] In the present invention, in the dry section (i.e., air layer) of dry-wet spinning, a certain amount of coagulant droplets with low coagulation value generated by an ultrasonic atomizer are introduced with nitrogen as carrier gas, and the droplets contact the surface of the stock solution stream extruded through the spinneret in the air layer to form gel points distributed in a point shape. The gel points are only distributed on the surface of the spinning solution stream, and will not affect the elimination of the extrusion expansion effect in the air layer and the spinneret drafting, so that a high spinning speed can still be maintained, and the gel points can form a groove structure basically arranged along the axial direction of the fiber in the subsequent coagulation and drafting process. Based on this, the preparation method described in the present invention can combine the advantages of wet and dry-wet spinning, can maintain a high spinning speed, and can form a groove structure on the surface of the original fiber, thereby improving the interlaminar shear strength of the composite material.

[0048] In a preferred embodiment, the spinning solution is a dimethyl sulfoxide solution of polyacrylonitrile copolymer.

[0049] More preferably, the viscosity average molecular weight of the polyacrylonitrile copolymer is 80,000-150,000; specifically, it may be 80,000, 90,000, 100,000, 110,000, 120,000, 130,000, 140,000 or 150,000.

[0050] In a preferred embodiment, the spinning solution can be obtained by polymerizing a polymerizable monomer containing acrylonitrile in dimethyl sulfoxide.

[0051] More preferably, based on the total weight of the polymerized monomer and dimethyl sulfoxide, the content of the polymerized monomer is 19-22% by weight.

[0052] In a preferred embodiment, the content of acrylonitrile in the polymerized monomer is 97-99 wt %.

[0053] More preferably, the polymerizable monomers further contain monomers that are conventionally used in the art and can be copolymerized with acrylonitrile, for example, itaconic acid.

[0054] In a preferred embodiment, the method for preparing the spinning solution comprises: mixing a polymerizable monomer containing acrylonitrile and dimethyl sulfoxide, then adding an initiator to carry out a polymerization reaction, and then removing residual monomers and bubbles to obtain the spinning solution.

[0055] In a preferred embodiment, the coagulation bath is an aqueous solution of dimethyl sulfoxide (DMSO).

[0056] More preferably, the concentration of dimethyl sulfoxide in the coagulation bath is 25-35 wt %; more preferably 28-32 wt %.

[0057] More preferably, the temperature of the coagulation bath is 2-10°C.

[0058] In a preferred embodiment, the method for preparing polyacrylonitrile carbon fiber precursor further comprises: sequentially washing, hot water drawing, oiling, drying and densification, steam drawing, heat setting and collecting the coagulated fibers obtained by coagulation.

[0059] In the present invention, the water washing, hot water drawing, oiling, drying and densification, steam drawing, heat setting and yarn collection can be carried out in accordance with conventional methods in the art.

[0060] In a preferred embodiment, the method for preparing polyacrylonitrile carbon fiber precursor comprises the following steps:

[0061] (1) The spinning solution is formed by spinning a thin stream of the solution, which contacts the coagulant in the air layer and then enters the coagulation bath to coagulate to obtain coagulated fibers;

[0062] (2) washing the coagulated silk, hot water drawing, oiling, drying and densification, steam drawing, heat setting and collecting the silk in sequence;

[0063] Wherein, the coagulant is a small molecule alcohol compound.

[0064] In a preferred embodiment, the step (1) is carried out in a spinning and solidification device, Figure 1 The spinning and coagulation device comprises: a spinning assembly 1, a sealing cover 2 and a coagulation bath tank 3 arranged below the sealing cover 2; the spinning assembly 1 has a spinneret 11, and the spinneret 11 is arranged in the sealing cover 2; the sealing cover 2 has an inlet 21, and the inlet 21 is used to input carrier gas and coagulant droplets; the coagulation bath tank 3 is used to accommodate a coagulation bath, and the lower part of the sealing cover 2 extends below the coagulation bath liquid surface.

[0065] In the present invention, the sealing cover 2 is open at the bottom, and the lower part of the sealing cover 2 is extended below the surface of the coagulation bath, so that the spinneret 11 and the air layer can be placed in a closed space, so that the coagulant droplets entering through the inlet 21 of the sealing cover 2 can contact the surface of the raw liquid flow squeezed out by the spinneret 11 in the air layer.

[0066] More preferably, a guide roller 31 is provided in the coagulation bath 3 .

[0067] Further preferably, the spinning and coagulation device further comprises a carrier gas storage tank 4, and the carrier gas storage tank 4 is used to provide carrier gas.

[0068] Further preferably, the spinning and coagulation device further comprises an ultrasonic atomizer 5, and the ultrasonic atomizer 5 is used to provide coagulant droplets.

[0069] In a preferred embodiment, the atomization rate of the coagulant droplets entering the sealing cover is 0.2-1.5 mL / min, more preferably 0.5-1 mL / min; specifically, it can be 0.5 mL / min, 0.6 mL / min, 0.7 mL / min, 0.8 mL / min, 0.9 mL / min or 1 mL / min.

[0070] In a preferred embodiment, the flow rate of the carrier gas entering the sealing cover is 30-80 mL / min.

[0071] The second aspect of the present invention provides polyacrylonitrile carbon fiber precursor prepared by the method described above.

[0072] A third aspect of the present invention provides a carbon fiber, which is obtained by pre-oxidation and carbonization of the carbon fiber precursor described above.

[0073] The present invention will be described in detail below through examples, but the protection scope of the present invention is not limited thereto.

[0074] Step (1) in the following Examples 1-5 is carried out in the following spinning and coagulation device, in conjunction with reference to Figure 1 The spinning and coagulation device comprises: a spinning assembly 1, a sealing cover 2, a coagulation bath tank 3 arranged below the sealing cover 2, a carrier gas storage tank 4 and an ultrasonic atomizer 5; the spinning assembly 1 has a spinneret 11, and the spinneret 11 is arranged in the sealing cover 2; the sealing cover 2 has an inlet 21, and the inlet 21 is used to input carrier gas and coagulation agent droplets; the coagulation bath tank 3 is used to accommodate a coagulation bath, and the lower part of the sealing cover 2 extends below the coagulation bath liquid surface; a guide roller 31 is arranged in the coagulation bath tank 3; the carrier gas storage tank 4 is used to provide carrier gas, and the ultrasonic atomizer 5 is used to provide coagulation agent droplets.

[0075] Example 1

[0076] (1) 10 kg of acrylonitrile (AN), 150 g of itaconic acid (IA) and 40 kg of DMSO were placed in a polymerization kettle and mixed evenly, that is, based on the total weight of the polymerization monomers (acrylonitrile and itaconic acid) and DMSO, the content of the polymerization monomers was 20.2% by weight, and the content of acrylonitrile in the polymerization monomers was 98.5% by weight. Then, polymerization was initiated by azobisisobutyronitrile (AIBN) at 65° C., and the amount of initiator added was 0.43% of the total weight of the system. After polymerization for 12 hours, residual monomers and bubbles were removed to obtain a spinning solution, and the viscosity-average molecular weight of the polyacrylonitrile copolymer in the spinning solution was 87,000;

[0077] The spinning stock solution is spun by the spinning assembly 1 to form a stock solution fine flow, which contacts with the coagulant (methanol) droplets in the air layer (height of 5 mm), and then enters the coagulation bath to coagulate and stretch 3 times to obtain coagulated fibers; wherein the coagulant droplets are generated by the ultrasonic atomizer 5 and the carrier gas provided by the carrier gas storage tank 4 is introduced from the inlet 21 of the sealing cover 2, and the flow rate of the coagulant droplets when introduced is 0.5 mL / min and the carrier gas flow rate is 50 mL / min; the coagulation bath is an aqueous solution of DMSO with a concentration of 30% by weight and a temperature of 5°C;

[0078] (2) The coagulated filaments were washed with water at 65°C, then stretched 2.5 times in water at 90°C, oiled, dried by a hot roller at 150°C for densification, then stretched 4 times in a steam stretching machine, heat-set and shrunk by 5%, and then rolled up to obtain polyacrylonitrile carbon fiber precursor with a fineness of 1.22 detex.

[0079] The carbon fiber strength obtained by conventional pre-oxidation and carbonization of the polyacrylonitrile carbon fiber precursor is 5.2Gpa and the modulus is 245Gpa. The unidirectional fiber reinforced composite material is prepared with E-type epoxy resin as the matrix. The interlaminar shear strength (ILSS) of the unidirectional fiber reinforced plastic interlaminar shear strength test method according to the standard JC / T 773-(1982)1996 is 85MPa.

[0080] Example 2

[0081] The method described in Example 1 was followed to obtain polyacrylonitrile carbon fiber precursors, with the flow rate of the coagulant droplets adjusted to 1 mL / min.

[0082] The strength of the carbon fiber obtained by pre-oxidation and carbonization of the polyacrylonitrile carbon fiber precursor is 4.9 Gpa, and the modulus is 242 Gpa. The unidirectional fiber reinforced composite material is prepared with E-type epoxy resin as the matrix. The interlaminar shear strength (ILSS) of the unidirectional fiber reinforced plastic interlaminar shear strength test method according to the standard JC / T 773-(1982)1996 is 90 MPa.

[0083] Example 3

[0084] The method described in Example 1 was used, except that the coagulant was ethanol, to obtain polyacrylonitrile carbon fiber precursor.

[0085] The strength of the carbon fiber obtained by pre-oxidation and carbonization of the polyacrylonitrile carbon fiber precursor is 5.3Gpa, and the modulus is 247Gpa. The unidirectional fiber reinforced composite material is prepared with E-type epoxy resin as the matrix. The interlaminar shear strength (ILSS) of the unidirectional fiber reinforced plastic interlaminar shear strength test method according to the standard JC / T 773-(1982)1996 is 80MPa.

[0086] Example 4

[0087] (1) 10 kg of acrylonitrile (AN), 300 g of itaconic acid (IA) and 40 kg of DMSO were put into a polymerization kettle and mixed evenly, that is, based on the total weight of the polymerization monomers (acrylonitrile and itaconic acid) and DMSO, the content of the polymerization monomers was 20.4% by weight, and the content of acrylonitrile in the polymerization monomers was 97% by weight, and then polymerization was initiated by AIBN at 65° C., and the amount of initiator added was 0.43% of the total weight of the system. After polymerization for 12 hours, residual monomers and bubbles were removed to obtain a spinning solution, and the viscosity-average molecular weight of the polyacrylonitrile copolymer in the spinning solution was 79,000;

[0088] The spinning stock solution is spun by the spinning assembly 1 to form a stock solution fine flow, which contacts with the coagulant (methanol) droplets in the air layer (height is 7 mm), and then enters the coagulation bath to coagulate and stretch 3 times to obtain coagulated fibers; wherein the coagulant droplets are generated by the ultrasonic atomizer 5 and the carrier gas provided by the carrier gas storage tank 4 is introduced from the inlet 21 of the sealing cover 2, and the flow rate of the coagulant droplets when introduced is 0.5 mL / min and the carrier gas flow rate is 50 mL / min; the coagulation bath is an aqueous solution of DMSO with a concentration of 30% by weight and a temperature of 5°C;

[0089] (2) The coagulated filaments were washed with water at 65°C, then stretched 2.5 times in water at 90°C, oiled, dried by a hot roller at 150°C for densification, then stretched 4 times in a steam stretching machine, heat-set and shrunk by 5%, and then rolled up to obtain polyacrylonitrile carbon fiber precursor with a fineness of 1.20 detex.

[0090] The carbon fiber strength obtained by conventional pre-oxidation and carbonization of the polyacrylonitrile carbon fiber precursor is 4.9Gpa and the modulus is 240Gpa. The unidirectional fiber reinforced composite material is prepared with E-type epoxy resin as the matrix. The interlaminar shear strength (ILSS) of the unidirectional fiber reinforced plastic interlaminar shear strength test method according to the standard JC / T 773-(1982)1996 is 78MPa.

[0091] Example 5

[0092] (1) 10 kg of acrylonitrile (AN), 100 g of itaconic acid (IA) and 40 kg of DMSO were placed in a polymerization reactor and mixed evenly, that is, based on the total weight of the polymerization monomers (acrylonitrile and itaconic acid) and DMSO, the content of the polymerization monomers was 20.2% by weight, and the content of acrylonitrile in the polymerization monomers was 99% by weight, and then polymerization was initiated by AIBN at 65° C., and the amount of initiator added was 0.43% of the total weight of the system. After polymerization for 12 hours, residual monomers and bubbles were removed to obtain a spinning solution, and the viscosity-average molecular weight of the polyacrylonitrile copolymer in the spinning solution was 89,000;

[0093] The spinning stock solution is spun by the spinning assembly 1 to form a stock solution fine flow, which contacts with the coagulant (methanol) droplets in the air layer (height of 5 mm), and then enters the coagulation bath to coagulate and stretch 3 times to obtain coagulated fibers; wherein the coagulant droplets are generated by the ultrasonic atomizer 5 and the carrier gas provided by the carrier gas storage tank 4 is introduced from the inlet 21 of the sealing cover 2, and the flow rate of the coagulant droplets when introduced is 1 mL / min and the carrier gas flow rate is 50 mL / min; the coagulation bath is an aqueous solution of DMSO with a concentration of 30% by weight and a temperature of 5°C;

[0094] (2) The coagulated filaments were washed with water at 65°C, then stretched 2.5 times in water at 90°C, oiled, and densified by hot roller drying at 150°C. Then, the filaments were stretched 4 times in a steam stretching machine, heat-set and shrunk by 5%, and then rolled up to obtain polyacrylonitrile carbon fiber precursor with a fineness of 1.23 detex.

[0095] The carbon fiber strength obtained by conventional pre-oxidation and carbonization of the polyacrylonitrile carbon fiber precursor is 5.2Gpa and the modulus is 250Gpa. The unidirectional fiber reinforced composite material is prepared with E-type epoxy resin as the matrix. The interlaminar shear strength (ILSS) of the unidirectional fiber reinforced plastic interlaminar shear strength test method according to the standard JC / T 773-(1982)1996 is 85MPa.

[0096] Comparative Example 1

[0097] The same spinning solution as in Example 1 was used to prepare the precursor by conventional dry-wet spinning process, and the specific process was as follows:

[0098] (1) The spinning solution formed by spinning the solution fine stream passes through an air layer (5 mm) and directly enters a coagulation bath for coagulation and drawing 3 times to obtain a coagulated filament; the coagulation bath is the same as that in Example 1;

[0099] (2) The coagulated filaments were washed with water at 65°C, then stretched 2.5 times in water at 90°C, oiled, and densified by hot roller drying at 150°C. Then, the filaments were stretched 4 times in a steam stretching machine, heat-set and shrunk by 5%, and then rolled up to obtain polyacrylonitrile carbon fiber precursor with a fineness of 1.22 dtex.

[0100] The strength of the carbon fiber obtained by pre-oxidation and carbonization of the polyacrylonitrile carbon fiber precursor is 5.1 Gpa, and the modulus is 244 Gpa. The unidirectional fiber reinforced composite material is prepared with E-type epoxy resin as the matrix. The interlaminar shear strength (ILSS) of the unidirectional fiber reinforced plastic interlaminar shear strength test method according to the standard JC / T 773-(1982)1996 is 65 MPa.

[0101] Test Example 1

[0102] The polyacrylonitrile precursors prepared in the examples and comparative examples were characterized using SEM, wherein the characterization results of the precursors prepared in Example 1 are as follows: Figure 2-3 As shown, the characterization results of the raw silk prepared in Example 2 are as follows Figure 4-5 As shown, the characterization results of the raw silk prepared in Comparative Example 1 are as follows Figure 6-7 shown.

[0103] Depend on Figure 2-7 It can be seen that the polyacrylonitrile carbon fiber precursor prepared by the method described in the present invention has a groove structure basically arranged along the fiber axis, and the groove is relatively short, which can be inferred to be formed by the point-shaped gel after multiple stretching. The groove structure is retained in the pre-oxidation carbonization, which is conducive to forming an anchoring effect with the resin matrix when preparing the composite material, enhancing the interlayer shear strength, and facilitating the transfer of loads and the performance of carbon fiber.

[0104] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing polyacrylonitrile carbon fiber precursor, characterized in that: The method comprises: a spinning solution fine flow formed by spinning solution contacts with a coagulant in an air layer, and then enters a coagulation bath for coagulation; The coagulant is a small molecule alcohol compound.

2. The method according to claim 1, characterized in that: The small molecule alcohol compound is a C1-C5 fatty alcohol; Preferably, the small molecule alcohol compound is selected from one or more of methanol, ethanol and n-propanol.

3. The method according to claim 1 or 2, characterized in that: The coagulant is coagulant droplets; Preferably, the coagulant droplets are generated by an ultrasonic atomizer.

4. The method according to claim 3, characterized in that: The diameter of the coagulant droplets is 0.5-5 μm.

5. The method according to any one of claims 2 to 4, characterized in that: The coagulant droplets are transported into the air layer by a carrier gas; Preferably, the carrier gas is nitrogen.

6. The method according to claim 1, characterized in that The height of the air layer is 3-10 mm, preferably 5-8 mm.

7. The method according to any one of claims 1 to 6, characterized in that: The spinning solution is a dimethyl sulfoxide solution of polyacrylonitrile copolymer; Preferably, the viscosity average molecular weight of the polyacrylonitrile copolymer is 80,000-150,000.

8. The method according to claim 7, characterized in that The spinning solution is obtained by polymerizing acrylonitrile-containing polymerization monomers in dimethyl sulfoxide; Preferably, the content of the polymerized monomer is 19-22 wt % based on the total weight of the polymerized monomer and dimethyl sulfoxide; Preferably, the content of acrylonitrile in the polymerized monomer is 97-99% by weight.

9. The method according to claim 1, characterized in that: The coagulation bath is an aqueous solution of dimethyl sulfoxide; Preferably, the concentration of dimethyl sulfoxide in the coagulation bath is 25-35 wt %; Preferably, the temperature of the coagulation bath is 2-10°C.

10. Polyacrylonitrile carbon fiber precursor prepared by the method according to any one of claims 1 to 9.

11. A carbon fiber, characterized in that: The carbon fiber is obtained by pre-oxidizing and carbonizing the carbon fiber precursor according to claim 10.

Citation Information

Patent Citations

  • A method for preparing polyacrylonitrile-based carbon fiber precursor

    CN104088029B

  • High-speed dry-spray spinning method for preparing deformed section carbon fiber precursor fiber, pre-oxidized fiber or carbon fiber

    CN109537106A

  • Vertical atomized chemical fiber molding method

    CN101988217A

  • Coagulation-bath-free spinning method of polyacrylonitrile-based carbon fiber protofilament

    CN102352537A

  • Preparation method of polyacrylonitrile-based carbon fiber precursor

    CN104088029A

Cited By

  • Carbon fiber with micro-groove structure and preparation method thereof

    CN121428702A